Blood, sweat, and tears: a review of the hematophagous, sudophagous, and lachryphagous Lepidoptera. Issue 2 (December 2013) - Plotkin, David; Goddard, Jerome
ABSTRACT Although adult Lepidoptera are not often considered medically relevant, some butterflies and moths are notorious for their consumption of mammalian body fluids. These Lepidoptera can be blood‐feeding (hematophagous), tear‐feeding (lachryphagous), or sweat‐feeding (we use the term "sudophagous"). Blood‐feeding Lepidoptera have been observed piercing the skin of their hosts during feeding, while tear‐feeding Lepidoptera have been observed frequenting the eyes of hosts in order to directly obtain lachrymal fluid. These behaviors have negative human health implications and some potential for disease transmission. In this study, articles concerning feeding behavior of blood, sweat, and tear‐feeding Lepidoptera were reviewed, with emphasis on correlations between morphological characters and feeding behaviors. Harmful effects and vector potential of these Lepidoptera are presented and discussed.